Virtually No Thoracic Lesion Inaccessible: A Pictorial Case Review - Pua, Bradley B.; Li, David; Sullivan, Brian W.; Madoff, David C. (Seminars in Interventional Radiology, 2013)
Access route considerations in percutaneous intrathoracic biopsy or ablation offers its own unique set of challenges, with special consideration toward reducing the rate of pneumothorax. This review highlights several novel and atypical methods to improve access to intrathoracic lesions through a series of representative cases. These methods include patient positioning, curved needles, hydrodissection, induced/artificial pneumothorax, and use of specialized equipment functions. No intrathoracic lesion should be considered “inaccessible” either for biopsy or treatment by percutaneous approaches without consideration of performing these adjunctive techniques.
Keywords: biopsy; ablation; lung cancer; thoracic; technique; interventional radiology